Provisional COVID-19 infrastructure induces large, rapid increases in cycling. - Kraus, Sebastian; Koch, Nicolas (My University, 2021)
The bicycle is a low-cost means of transport linked to low risk of transmission of infectious disease. During the COVID-19 crisis, governments have therefore incentivized cycling by provisionally redistributing street space. We evaluate the impact of this new bicycle infrastructure on cycling traffic using a generalized difference in differences design. We scrape daily bicycle counts from 736 bicycle counters in 106 European cities. We combine these with data on announced and completed pop-up bike lane road work projects. Within 4 mo, an average of 11.5 km of provisional pop-up bike lanes have been built per city and the policy has increased cycling between 11 and 48% on average. We calculate that the new infrastructure will generate between $1 and $7 billion in health benefits per year if cycling habits are sticky.
Keywords: Fahrradverkehr; Fahrradweg; Stadtverkehr; Straßenverkehr; Verkehrsinfrastruktur; Pop-up-Radweg; Corona-Krise